Early Jurassic A-type granite and monzodiorite from the Baoji batholith: Implication for tectonic transition from post-collision to post-orogenic extension in the Qinling Orogenic Belt, China - Gong, Xiangkuan; Abuduxun, Nijiati; Jia, Xiaoliang; Cheng, Yuanfeng; Cai, Hongming; Wu, Xueqian; Yang, Haodong (Frontiers in Earth Science, 2024)
The early Jurassic granitoids in the Qinling Orogenic Belt (QOB) play a crucial role in understanding the tectonic implications for the geological evolution of China. To elucidate the early Jurassic tectonic setting of QOB, we performed a comprehensive analysis of zircon U-Pb ages, whole-rock geochemistry, and in situ zircon Lu-Hf isotopes from early Jurassic monzodiorite and K-feldspar granite within the Baoji batholith in western QOB. The intrusions yielded zircon U-Pb ages of 186 ±2 Ma and 188 ±2 Ma, respectively. The monzodiorites are characterized by relatively high MgO, Rb, Th, U, and LREE contents, as well as low P, Ti, and HREE contents. They also exhibit high Nb/Ta ratios (20.6-23.4). The zircon εHf(t) values for the monzodiorite sample range from -4.36 to 6.47, indicating significant contributions from a fertile continental lithospheric mantle with the involvement of crustal components. The Kfeldspar granites are enriched in K2O + Na2O, Rb, Zr, Hf, and Nb, and lower Ba, Sr, Ti, and P. They exhibit high Nb/Ta and Ga/Al ratios but low Y/Nb and Yb/Ta ratios. Their geochemical characteristics reveal an A-type granite affinity with elevated zircon saturation temperatures (848-900 °C). Additionally, the K-feldspar granite exhibits REE and trace element patterns similar to those observed in the monzodiorite. However, a wide range of zircon εHf(t) values (-4.72 to 3.98), differing from those of the monzodiorite, indicate that the parental magma of the K-feldspar granite experienced magma mixing between a monzodioritic magma and a crustal-derived felsic magma. These findings suggest that both A-type K-feldspar granite and monzodiorite likely formed during post-orogenic processes. Additionally, the QOB commenced its postorogenic evolution as an extensional tectonic environment during the early Jurassic period.